Effects of carpofen and chondroitin sulphate in thyroid function tests in dogs with musculoskeletal - Cardoso, Mauro Jose Lahm; Zacarias, Francielle Freitas Gibson Silva; Melussi, Maira; Fagnani, Rafael; Oba, Eunice [UNESP]; Costa, Fabiano Sellos; Ibanez, Jose Fernando (My University, 2014)
Several non-thyroid factors such as age, breed, concomitant diseases and use of certain drugs might influence the diagnosis of hypothyroidism in dogs. Changes in the concentrations of thyroid hormones due to non-thyroid illnesses or drugs are named euthyroid sick syndrome. The aim of this study is to evaluate the thyroid function in dogs with musculoskeletal diseases or without musculoskeletal diseases receiving carprofen and chondroitin sulphate, glucosamine, collagen, ascorbic acid and manganese sulphate. A total of 43 dogs were used, divided into three groups: 20 dogs in the Carprofen Group (GC), 20 dogs in the Chondroitin Sulphate Group (GSC) and 15 dogs in the placebo group (GP). The animals included in the GC group were previously diagnosed with degenerative joint disease. Dogs in the GSC and GP groups did not present joint diseases or a diagnosis of systemic disease. Dogs in the GC group received daily 2.2 mg kg-1 carprofen during 60 days, twice a day. The dogs in the GSC group received daily chondroitin sulphate (30 mg kg-1) and association (glucosamine, collagen, ascorbic acid, manganese sulphate) during 60 days, twice a day. Dogs in the GP group received daily 10 mg kg-1 corn starch in capsule during 60 days, twice a day. The animals were evaluated in five Moments (M), the initial Moment (M0), before the first administration, resulting in basal values within the parameters studied; at 15 days (Ml), at 30 days (M2), at 45 days (M3) and at 60 days (M4). The measurements of thyroid function (total thyroxine-TT4, free thyroxine-FT4, thyrotropin-TSH) were performed in the five moments. In the control group the M's had an effect on TT4 and FT4 with reduced concentrations of TT4 below the reference values. In the SC group, the M's had an effect only on the FT4 and the highest average was observed in M4. Carprofen in dose for 60 days promoted the reduction of serum TT4 in dogs with musculoskeletal diseases. Therefore, the strain caused the TT4 would be consistent with hypothyroidism. Recommend discontinuation of therapy with carprofen for a minimum period of 15-30 days before the tests of thyroid function to be interference. While chondroitin sulfate at the dose and duration used does not alter thyroid function.
Keywords: ATNES; Euthyroid; FT4; Hypthyroidism; Non-thyroid illnesses